Modeling Analysis of Arts and Culture Interest in Student Communities in Banyumas Using Talent Interest Matrix - Hapsari, Ariadne Tiara; Banatuzka, Khurida (Universitas Amikom Purwokerto, 2024)
Good leadership helps maximize the use of resources to achieve organizational goals. Data shows that this comes from young people who are enrolling in colleges in the Banyumas area. The local government, from the village to the region, plans a way so that local arts and culture are not easily influenced by other cultures. This method is used by the local government to encourage young people at the college level to improve community activities and college student activity programs. When the organization looks less professional, this problem arises. This is caused by a number of main factors, including problems related to the vision and mission, especially in managing the organization itself. Organizations founded by young people can face various unique problems due to the dynamics and unique characteristics of young members. Based on the problems found in the previous situation analysis, it is necessary to provide counseling and guidance to young students. This is especially true for students who are members of groups and communities in the college environment. This community organization focuses on the context of arts and culture in the Banyumas area, Central Java. Solutions must be used to address problems to improve leadership in organizations managed by young people. The first thing we do is provide an important understanding of leadership in organizations, then we go into the content, namely about arts and culture in the Banyumas region of Central Java.